Assessment of antiobesity effect of folic acid on induced obese rats / Intan Nur Shafika Abd Kadir - Abd Kadir, Intan Nur Shafika (2014)
Obesity is one of the major risk factor in the world that can cause many underlying diseases such as diabetes mellitus and cardiovascular diseases. Meanwhile, folic acid is predicted to have certain effects on lipid reducing activity and haematological analysis. The aim of this study was to examine the direct effects of folic acid in reducing the precursor factors of obesity by determining the anthropometrical parameters, biochemistry parameters and haematological parameters associated with obesity in experimental rats. There are five groups of obese female rats, each with different dose of treatment within 14 days. Group 1 until group 4 were treated with 2, 5, 10 and 20 mg/kg, respectively. The control group, group 5 was treated with normal saline. The biochemistry parameters including cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL) and triglycerides levels has been analysed using ILab Chemistry Analyzer 300 PLUS. The haematological analyses were done using Beckman Coulter International S.A COULTER® LH 500. To induce obesity, the female rats has been induce with ovariectomy surgical procedures. The results were analyzed by using One Way ANNOY A of SPSS 201h version in order to see the significance difference between the treated and the control group. In the anthropometrical studies, only the water intakes of the experimental rats had increased significantly in day 14, between the group 2 (5 mg/kg folate) and group 3 (10 mg/kg folate) and the control group. In biochemistry analysis, the cholesterol levels of group 1 (2 mg/kg folate) and group 2 (5 mg/kg folate) were significantly elevated as compared to the control group. As for the hematological analysis, only white blood cell counts (WBC) counts (group 1 and group 4), eosinophils, red blood cell (RBC) counts, hematocrytes, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and mean platelet volume (MPV) has significance difference as compared to the control groups but with variance of increase and decrease. In summary, the folate treated rats has no significance difference from the control group, but these findings could be a reference in order to further investigating the effects of oral folate treatment in different period and condition.